IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM PEMBINAAN PESERTA DIDIK - Fadillah, Ahmad Arif; Putri, Khilda Jumhadi; Nurafifah, Vianti Dinda; Safitri, Santi; Aisyah, Nanda; Aulia, Rahmatul; Salimah, Sumayya Mujahidah; Febriyani, Nur; Oktapiani, Rizka; Marctines, Gabriella Sinthia (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2022)
According to Government Regulation No. 87 of 2017 Article 3 regarding strengthening character education (PPK), namely PPK is carried out by applying the values of Pancasila in character education, especially including religious values, honesty, tolerance, discipline, hard work, independent creativity, democracy, curiosity, enthusiasm nationality, love for the homeland, appreciate achievements, communicative, love peace, love to read, care for the environment, care about social, and be responsible. This study aims to find out how the implementation of character education management in coaching students. This research is a literature study. In literature studies, researchers determine the research topic and determine the formulation of the problem, before they go into the field to collect the necessary data. In the National Long-Term Development Plan 2005-2025 (Law of the Republic of Indonesia Number 17 of 2007) states the realization of a strong, competitive, noble character and moral nation based on Pancasila which is characterized by the diverse character and behavior of humans and the Indonesian people, have faith and fear of God Almighty, tolerant virtuous, mutual cooperation, patriotic spirit, dynamic development, and science and technology oriented.